Implementation of Digital Marketing as A Strategy to Improve Marketing and Sales - Supriyatin, Wahyu; Wisesha, Kausar Japa (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
JerseyBolaku distro in Jatiasih, sells conventional and custom jersey. Marketing their products using conventional methods where customers come to see the product and make transactions. The owner wants product promotion, by word of mouth and through social media. The owner do manual bookkeeping by recording every incoming and outgoing product, so there is duplicate and inappropriate data. This makes owners changed the marketing strategy from conventional to digital. The purpose of this research is to distribution using digital marketing. The digital marketing strategy made by owners, used e-commerce website, where it can be accessed by customers anywhere using a smartphone. Customers need access the website if they want to view products and make transactions. Owners find it easy to view sales reports in each period. The method used in making the website is the SDLC method with a prototyping model. The steps taken in the prototyping model is to identifying needs and problems of user, hardware, software, determining the programming language, designing user interfaces for admins and users are using UML diagrams, the prototypes website need to be evaluated before launching and do evaluating and improving if any problems when tested and finally launched the system to be implemented. Website testing is done by using black box testing to test the functionality of the website. Website running successfully using Internet Explorer on PC and smartphone. Website successfully hosted, customers can view and order products more easier and faster. The owner can record sales transactions and record products in more detail.